Microbubble transport in water‐saturated porous media. Issue 6 (18th June 2015) - Ma, Y.; Kong, X.‐Z.; Scheuermann, A.; Galindo‐Torres, S. A.; Bringemeier, D.; Li, L.
Abstract Laboratory experiments were conducted to investigate flow of discrete microbubbles through a water‐saturated porous medium. During the experiments, bubbles, released from a diffuser, moved upward through a quasi‐2‐D flume filled with transparent water‐based gelbeads and formed a distinct plume that could be well registered by a calibrated camera. Outflowing bubbles were collected on the top of the flume using volumetric burettes for flux measurements. We quantified the scaling behaviors between the gas (bubble) release rates and various characteristic parameters of the bubble plume, including plume tip velocity, plume width, and breakthrough time of the plume front. The experiments also revealed circulations of ambient pore water induced by the bubble flow. Based on a simple momentum exchange model, we showed that the relationship between the mean pore water velocity and gas release rate is consistent with the scaling solution for the bubble plume. These findings have important implications for studies of natural gas emission and air sparging, as well as fundamental research on bubble transport in porous media.